Social pressures and their impact on smartphone use stickiness and use habit among adolescents - Haiqing Bai; Jiatong Liu; Wenshi Bai; Ting Cao (Heliyon, 2024)
Excessive smartphone use has become a growing issue among adolescents as they develop mentally and socially. While researchers have examined individual and technological predictors of smartphone addiction, few studies consider broader societal influences. This study explored how social pressures such as mimicry, coercion, and norms impact persistent conscious smartphone use (use stickiness) and unconscious smartphone use (use habit). A survey was administered in two phases to 309 college students at a university in Southern China to gather data on perceptions of social influences and their degree of smartphone overuse. The relationships were analysed using a structural equation model. The study confirms the impact of three social pressures - mimetic, coercive and normative - on adolescents’ degree of smartphone overuse (use stickiness and use habit). The mimetic pressure positively impacted use stickiness but not use habit. The coercive pressure positively impacted both the use stickiness and the use habit. The normative pressure positively impacted use habit but not use stickiness. This study provides a novel perspective on overlooked social drivers of problematic smartphone tendencies among youth. Our study also provides insights for educators, parents, and policymakers to more effectively intervene in adolescent smartphone overuse.